The Phenomenon of Normalization of Zina and Its Relevance to Ashrat al-Sa'ah: Analysis of al-Hajj verses 1-2 - Hendra Wibowo; Yeti Dahliana; Marsekal Rahman Hakiem (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: The phenomenon of increasing promiscuous sexual behavior in today's society shows a significant shift in moral values. The purpose of this study is to examine the correlation between this phenomenon and the commemoration of the Apocalypse in Surah Al-Hajj 1-2 and the saheeh hadiths related to Asyrat al-Sa'ah. Theoretical framework: This research refers to the approach of the study of Surah Al-Hajj verses 1-2, its correlation with the Punishment at the time of the Apocalypse. Literature review: Classical and Contemporary Interpretations combined with theories of social deviance. Method: This study uses a qualitative method with a literature approach, in the form of thematic interpretation and hadith studies, where the main source is Al-Hajj verses 1-2, and the secondary source is classical and contemporary tafsir books, as well as journals about Zina with semantic analysis.  Results: The results of the study show that there is a correlation between punishment and the Apocalypse (great), where the great apocalypse contains the greatest and most devastating set of punishments that have occurred since humans lived, and the thing that most affects the occurrence of punishment is acts that deviate from the rules of Allah SWT. Implications: This study highlights the importance of being aware of the rampant practice of adultery among the community as a form of caution for the coming of the Punishment and the Apocalypse. Novelty: This study offers a new perspective by linking the psychology of fear in Surah Al-Hajj 1-2 as a direct response to the normalization of adultery in the digital age, a correlation rarely discussed in contemporary sekaological literature.